HUBUNGAN ANOPHELES BARBIROSTRIS DENGAN MALARIA - Iryani, Krisna (LPPM Universitas Terbuka, 2011)
Malaria is a disease caused by intercellular obligate protozoa genus of Plasmodium which is a parasite carried by female Anopheles mosquito. One of them is Anopheles barbirostris. Research in several places already proved that Anopheles barbirostris acts as a vector of malaria. One case that occurred in Cineam district, Tasikmalaya regency showed that Anopheles barbirostris is suspected as vector of malaria. This is proven through a research on the relationship between Anopheles barbirostris with malaria. Data was taken from the larvae and adult mosquitoes captured around Cineam village, Tasikmalaya. The observation was done in the open field and laboratory. Data and identification by pictorial key for female Anopheles showed that the population of Anopheles barbirostris was always a dominant population compared to another Anopheles species. Because of the breeding ponds and the resting places were around the village, it is suspected that they mainly bit humans. The result of the observation in laboratory showed the life cycle of Anopheles barbirostris are around 20-27 days, and the longevity of 20 days. Morphological identification of Anopheles barbirostris by pictorial key for female Anopheles showed that there is no any significant difference. This research showed that Anopheles barbirostris was suspected as vector of malaria in Cineam village, Tasikmalaya.